Knowledge, Attitude, and Practice of Oral Health among School Children Aged 11–16 Years of an Urban Area - S. N. Ajas; Chandra S. Metgud (Journal of Primary Care Dentistry and Oral Health)
Background: Oral health has a great impact on health and wellbeing of individual in the society. About 90% of school children worldwide have experienced dental caries and is more prevalent in Latin American and Asian countries Aim: This study aims to assess the knowledge, attitude and practice of oral health among school children aged 11–16 years. Materials and Methods: A cross-sectional study was carried out among 800 school children aged 11–16 years from selected four co-educational schools of Belagavi city. Data were collected by personal interview using a predesigned and pretested questionnaire after obtaining written informed consent from parents and assent from students. Quantitative data were analyzed using mean, median and standard deviation (SD) and qualitative data were summarized as percentage and proportion. Results: Mean ± SD age of the participant was 13.5 ± 1.87 years and median age was 13.5 years. More than 60% had average knowledge and practice score regarding oral health. Mean ± SD knowledge and practice score was 12.67 ± 2.67 and 8.31 ± 1.51, respectively. Above 50% had positive attitude score towards oral health and mean ± SD attitude score was 5.21 ± 1.40. Conclusion: Each risk factor which is associated with poor oral health among the school children was completely preventable with adequate knowledge, attitude, and practice behavior. Hence, there is a need for regular oral health education to the children, as well as their parents and school teachers.